SINTESIS DAN UJI AKTIVITAS ANALGETIKA-ANTIINFLAMASI SENYAWA N-(4t-butilbenzoil)-p-aminofenol - Sri Sutji Susilowati; Santi Nur Handayani (Universitas Jenderal Soedirman, 2006)
The synthesis of N-4t-butyl benzoil-p-aminophenol has been done by reacting p-aminophenol and N-4t-butyl benzoil chloride compounds, then the products were isolated and analyzed by TLC, melting point determination, UV/Vis Spectrofotometry, infra red spectrofotometry and mass spectrometry. The synthesis yield of N-4t-butylbenzoil-p-aminophenol was 33,52%, with the compound melting point between 192-194 oCThe determination of analgesic (ED50 of % analgesic activity ) and anti inflammatory activity (ED50 of edema inhibition) gave the ED50 of % analgesic activity was 144 mg/kg and ED50 of % edema inhibition was 43,24 mg/kg.